Подготовка элитных специалистов в области техники и технологий; Вопросы образования; № 2 - Чубик П. С. Петр Савельевич; Чучалин А. И. Александр Иванович; Соловьёв М. А. Михаил Александрович; Замятина О. М. Оксана Михайловна (2013, 2013)
Заглавие с экрана